New directions for exploring the consequences of proactive behaviors: Introduction to the special issue. (13th January 2019) - Liu, Wu; Tangirala, Subrahmaniam; Lee, Cynthia; Parker, Sharon K.
Summary: This special issue introduces new directions for exploring the consequences of proactive behaviors. The authors summarize the new scopes of consequences, new social contexts, and new methods in this exploration. They also identify several limitations of the existing literature and call for more future research in this stream.